Fuzzy based back stepping controller for glucose level regulation under meal disturbance - Yousra Abd Mohammed; Rokaia Shalal Habeeb (Institute of Advanced Engineering and Science, 2022)
Diabetes is one of the most common and critical diseases around the world, which need insulin injections to control the body’s glucose rate. A robust back stepping (BS) controller design based on fuzzy system is introduced in this paper to control the glucose level with the presence of meal disturbance. The controller’s design is based on Bergman’s mathematical model. Different fuzzy controller structures are implemented (fuzzy PI, fuzzy PD, and fuzzy PID) controllers along with BS controller named as (BS-fuzzy PI, BS-fuzzy PD, BS-fuzzy PID) controllers. Simulation results using MATLAB/Simulink show efficiency and robustness of the proposed design in terms of controlling the insulin concentration level in blood under meal disturbance and retaining the glucose level to its Basal value.